1990
DOI: 10.1038/bjc.1990.380
|View full text |Cite
|
Sign up to set email alerts
|

Flow cytometry in primary breast cancer: improving the prognostic value of the fraction of cells in the S-phase by optimal categorisation of cut-off levels

Abstract: Summary The use of continuous prognostic variables is clinically impractical, and arbitrarily chosen cut-off points can result in a loss of prognostic information. Here we report findings from a study of primary breast cancer, showing how the prognostic value of the fraction of cells in the S-phase of the cell cycle (SPF), as measured by flow cytometry, can be affected by the SPF cut-off level(s) adopted. It was possible to evaluate the SPF in 566 (94%) of 603 consecutive cases where fresh frozen specimens wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
0

Year Published

1992
1992
2003
2003

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(20 citation statements)
references
References 20 publications
3
17
0
Order By: Relevance
“…SPF in the two samples manifested significant positive correlation (r, = 0.76; p < 0.001). Previous results obtained at our department have demonstrated that dividing a breast cancer series into three SPF categories (SPF < 7.0%; 7.0 5 SPF < 12% and SPF 2 12%), gave SPF the strongest prognostic value (36). In the present work, we have therefore used the same division into three SPF groups when studying the variation in SPF between the two samples from the same breast cancer specimen.…”
Section: Dna Analysis In Two Samples From One Tumor Specimen-correlatmentioning
confidence: 94%
“…SPF in the two samples manifested significant positive correlation (r, = 0.76; p < 0.001). Previous results obtained at our department have demonstrated that dividing a breast cancer series into three SPF categories (SPF < 7.0%; 7.0 5 SPF < 12% and SPF 2 12%), gave SPF the strongest prognostic value (36). In the present work, we have therefore used the same division into three SPF groups when studying the variation in SPF between the two samples from the same breast cancer specimen.…”
Section: Dna Analysis In Two Samples From One Tumor Specimen-correlatmentioning
confidence: 94%
“…Another approach has been to ignore this diploid dilutional effect and use raw S-phase, DS for DNA diploids and AS for DNA aneuploids, as a single prognostic variable (26,63). This method works very well because the DNA ploidy information is essentially embedded in the S-phase and they are both inversely correlated to relapse.…”
Section: S-phase Adjustmentsmentioning
confidence: 99%
“…For clinical purposes, however, cut-off levels are often adopted to define low and high SPF subgroups. At our laboratory, diploid tumours with an SPF value >,7.0% and non-diploid tumours with an SPF value >, 12 are classified as having high SPF, and the remainder as having low SPF (33). If these cut-off levels are applied in the present series, the concordance in SPF categories between F N A and biopsy materials would only be obtained in 68% (28/41) of cases overall, in 79% ( 1 1/14) of cases of diploid tumours, and 64% (14/22) of cases of nondiploid turnours.…”
Section: Discussionmentioning
confidence: 99%